Educação escolar indígena: processos de implementação e efetividade das políticas educacionais na comunidade Porto Praia de Baixo (Tefé-AM) - Oliveira , Nelma Catulino de (2022)
This research analyzes the implementation of public policies of indigenous school education between 2011 and 2021 and their effectiveness in the indigenous territory of Porto Praia de Baixo, Municipality of Tefé. The Municipality of Tefé, although it has only the indigenous land Barreira da Missão demarcated and recognized by the Brazilian State, concentrates numerous territories where the presence of indigenous peoples is significant and potential reference for their political mobilization processes in the Region of the Middle River Solimões and Tributaries, as it concentrates the presence of public institutions, being also reference in trade, health and education to neighboring municipalities. The objectives of this research were to contextualize the historical process of ethnic mobilization of indigenous peoples who contributed to the implementation of indigenous school education in the territory of Porto Praia de Baixo; Identify and characterize the public policies of school education implemented in the Porto Praia de Baixo community, from 2011 to 2021; and Analyze the effectiveness of the policies implemented for indigenous school education in the community context. We used the qualitative research method, as well as the bibliographic review, document analysis and semi-structured interviews; developing an interdisciplinary approach between the social sciences in dialogue with history and education. The analysis allowed us to highlight, from public policies for indigenous school education, an understanding of the dynamics between State and Society and, above all, how social movements (groups and social agents) contribute to the implementation and effectiveness of educational actions in the indigenous territory of the community of Porto Praia de Baixo.